KEPUASAN DAN LOYALITAS KONSUMEN TERASI UDANG CAP MAWAR DI KABUPATEN LAMPUNG TIMUR - Priyo Febriartiko Maulana; Adia Nugraha; Rabiatul Adawiyah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2026)
The aim of this study is to assess consumer satisfaction and loyalty and to highlight consumer behavior patterns regarding the purchase of Terasi Udang Cap Mawar in East Lampung Regency. This study was conducted in Pekalongan Market, Purbolinggo Market, Raman Utara Market, and Taman Cari Market. The inquiry method primarily utilized was a survey method. Accidental sampling was selected as the sampling method in this study. The number of respondents was 50 housewives. The data were analyzed using the Customer Satisfaction Index (CSI), Customer Loyalty Index (CLI), and descriptive analysis. The results showed that consumer satisfaction with product Terasi Udang Cap Mawar fell into the very satisfied category achieving a Customer Satisfaction Index (CSI) value of 81.68%. Furthermore, consumer loyalty towards Terasi Udang Cap Mawar was classified as loyal with a Customer Loyalty Index (CLI) value of 78.90%. The amount of consumer purchases of Terasi Udang Cap Mawar products was Rp 6,840/month with an average consumption of 16.3 packs/month. The frequency of consumer purchases was recorded as 2 times/month, while the frequency of consumption reached 4 times/month. The most common place to buy was at the nearest shop, with the main reason for consuming this shrimp paste being that they liked the taste.